2002
DOI: 10.1081/imm-120016242
|View full text |Cite
|
Sign up to set email alerts
|

ANTIBODIES AGAINST THE HUMAN HEAT SHOCK PROTEIN hsp70 IN PATIENTS WITH SEVERE CORONARY ARTERY DISEASE

Abstract: Heat shock proteins (hsps) play complex role in the function of the immune system, they can activate both humoral and cellular immune response, as well the complement system. Although autoimmunity to hsp70 was implicated in certain autoimmune diseases and other conditions, the exact role of anti-hsp70 antibodies is not known. It was demonstrated by our previous work and other's findings that antibodies against the 60 kDa hsps are strongly associated with coronary atherosclerosis and carotis disease. It is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…after angioplasty have been documented in several studies (5,15,(22)(23)(24), but the results are inconsistent (2,(4)(5)(6)(7). Our study is the largest case control study so far on the relationship between anti-Hsp60 and risk of CHD, providing evidence that increasing anti-Hsp60 concentrations are associated with CHD risk in a doseresponsive manner.…”
Section: Discussionmentioning
confidence: 63%
“…after angioplasty have been documented in several studies (5,15,(22)(23)(24), but the results are inconsistent (2,(4)(5)(6)(7). Our study is the largest case control study so far on the relationship between anti-Hsp60 and risk of CHD, providing evidence that increasing anti-Hsp60 concentrations are associated with CHD risk in a doseresponsive manner.…”
Section: Discussionmentioning
confidence: 63%
“…[14][15][16][17] It has been reported that anti-Hsp-70 titres are not elevated in subjects with severe coronary atherosclerosis, whereas titres to Hsp-60 and -65 were significantly raised in these patients. 15,17 It has also been reported that patients with type 2 diabetes mellitus have significantly higher anti-Hsp titres compared with non-diabetic controls.…”
Section: Discussionmentioning
confidence: 94%
“…There have been numerous previous reports on the (Xu et al 1999(Xu et al , 2000Burian et al 2001;Zhu et al 2001;Kocsis et al 2002;Wysocki et al 2002). For instance, a prospective study has indicated that antibody titers to Hsp60 are predictive of cardiovascular events (Huittinen et al 2002).…”
Section: Discussionmentioning
confidence: 99%